Gophers Spermophilus suslicus (Guldenst., 1769) and Spermophilus pygmaeus (Pallas, 1778) at the junction of their areas (Report 1. Past distribution) - Токарський, В. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
On the territory of Kharkiv region there are two species of gophers – Spermophilus suslicus and Spermophilus pygmaeus, more common is S. pygmaeus. It was revealed, that for two centuries the number of gophers changed several times. Periods of high values did not exceed three decades each (the end of XVIII century, the middle of ХIХ century, 1880–1900 years, 1920–1950 years).